Four-Leaf Clovers - Ángel Pes (Acción Empresarial)
" ""Responsible businesses are economic institutions which are committed to the values of our society. But it turns out that not all companies making that claim really have respect for human rights, decent working conditions, environmental protection and the elimination of corruption in their DNA; and these are the principles of the United Nations Global Compact. In this practical, flexible and sorely needed book, Angel Pes has mustered the necessary courage to explain how to sow and grow these values in ourorganisations, while simultaneously contributing to the material development of societies as they achieve their goal - the creation of economic value. Using the metaphor of the four-leaf clover, he explains that all companies create value to subsist in the medium and long term, but not all of them possess the other three leaves: a specific purpose which is subject to no particular interest group; a tradition of behaviour patterns based on integrity and transparency; and a commitment to tackling the social and environmental challenges of our times. Fortunately, the frequency of four-leaf clovers in the business ecosystem is much greater than it is on our lawns, and it can also be encouraged to increase still further if we create the right environment for it. When you read this book, with the descriptions of the success stories of Unilever, Repsol and CaixaBank, you will discover how your company can be turned into a symbol of good fortune for the community."""